Chemical composition of manganese nodules and ferromanganese crusts using Atomic absorption analysis - Kennecott Corporation (PANGAEA, 2023)
In the mid 1970s Kennecott Exploration, Inc. conducted various systematic studies on the chemical composition of manganese nodules and crusts in order to determine the variability of their composition. They ultimately prepared a "normalised" manganese sample numbered GRLD-126 (see: Meylan, Maurice A (2022): Kennecott Standard GRLD-126 manganese nodule replicate Atomic absorption spectrophotometry (AAS) analyses, https://doi.pangaea.de/10.1594/PANGAEA.948422). The present dataset compiled by NOAA-NCEI is devoted to the extensive analysis of mostly buried in cores manganese deposits recovered by the R/V Robert Conrad and the R/V Vema from the Lamont-Doherty Earth Observatory (LDEO). Samples were analysed by the atomic absorption spectrophotometry by Kennecott Exploration, Inc.